Anhydrous Phase B: Transmission Electron Microscope Characterization and Elastic Properties. (14th August 2019) - Addad, A.; Carrez, P.; Cordier, P.; Jacob, D.; Karato, S.‐I.; Mohiuddin, A.; Mussi, A.; Nzogang, B. C.; Roussel, P.; Tommasi, A.
Key Points: Anhydrous phase B and stishovite formed directly from olivine in experiments at 14 GPa and 1400 °C The structure of anhydrous phase B is determined ab initio from precession electron diffraction tomography in transmission electron microscopy Elastic and seismic properties of anhydrous phase B are calculated Abstract: We have performed an extensive characterization by transmission electron microscopy (including precession electron diffraction tomography and ab initio electron diffraction refinement as well as electron energy loss spectroscopy) of anhydrous phase B (Anh‐B) formed directly from olivine at 14 GPa, 1400 °C. We show that Anh‐B, which can be considered as a superstructure of olivine, exhibits strong topotactic relationships with it. This lowers the interfacial energy between the two phases and the energy barrier for nucleation of Anh‐B, which can form as a metastable phase. We have calculated the elastic and seismic properties of Anh‐B. From the elastic point of view, Anh‐B appears to be more isotropic than olivine. Anh‐B displays only a moderate seismic anisotropy quite similar to the one of wadsleyite. Plain Language Summary: Anhydrous phase B (Anh‐B) is a dense magnesium silicate with composition (Mg, Fe)14 Si5 O24, which is expected to form in Mg‐rich or Si‐depleted regions of the mantle. We show that due to strong crystallographic similarities with the crystal structure of olivine, it can form directly from it as a metastable phase. We show that Anh‐B exhibits a moderate seismic anisotropy, which makes its detection difficult in the mantle.